2011
DOI: 10.1186/1746-1596-6-107
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between DNA ploidy, metaphase high-resolution comparative genomic hybridization results and clinical outcome of synovial sarcoma

Abstract: BackgroundAlthough synovial sarcoma is the 3rd most commonly occurring mesenchymal tumor in young adults, usually with a highly aggressive clinical course; remarkable differences can be seen regarding the clinical outcome. According to comparative genomic hybridization (CGH) data published in the literature, the simple and complex karyotypes show a correlation between the prognosis and clinical outcome. In addition, the connection between DNA ploidy and clinical course is controversial. The aim of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
0
12
0
2
Order By: Relevance
“…Aneuploidy can be stemline or single‐cell aneuploidy 1,4,10,11 . Stemlines with modal values <1.8c, >2.2c and <3.6c or >4.4c reflect stemline aneuploidy.…”
Section: Introductionmentioning
confidence: 95%
“…Aneuploidy can be stemline or single‐cell aneuploidy 1,4,10,11 . Stemlines with modal values <1.8c, >2.2c and <3.6c or >4.4c reflect stemline aneuploidy.…”
Section: Introductionmentioning
confidence: 95%
“…Many studies in humans [28,30,31,62] reported a similar correlation, although this is not universal [58]. Striking was the absolute lack of a relation between ploidy status and risk of metastasis in OS, which is in contrast to OS in humans [32,63].…”
Section: Discussionmentioning
confidence: 96%
“…Striking was the absolute lack of a relation between ploidy status and risk of metastasis in OS, which is in contrast to OS in humans [32,63]. In diploid cases within particular types of cancer more detailed cytogenetic analyses are required to discern those changes that predict metastatic behavior [62,64]. …”
Section: Discussionmentioning
confidence: 99%
“…A betegség kiújulására akár 20 év múlva is számítani lehet. Az áttétek predilekciós helyei a következők: tüdő (74-81%), nyirokcsomók (3-23%) és a csont (10-20%) [39].…”
Section: Megbeszélésunclassified